Assessing the Work Performance of Vocational High School Teachers in Gunung Kidul: A Survey (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
This study aims to evaluate the work performance of vocational high school (SMK) teachers in Gunung Kidul District, identifying strengths, weaknesses, and factors influencing their performance. It also aims to provide recommendations for improving vocational education quality in the region. Using a survey method with a qualitative descriptive approach, the study focuses on assessing chemistry teachers’ performance in SMKs in Gunung Kidul. Data were collected via a validated questionnaire covering 4 aspects and 11 indicators. Analysis involved descriptive qualitative methods and literature review. The survey included 32 chemistry teachers, predominantly female (65.62%), aged 21-30 years (46.88%), with teaching experience under 5 years (62.50%). Evaluation of teachers’ performance focused on quality of work, quantity of results, knowledge of job tasks, and collaboration. Results showed overall high compliance with standards and efforts to achieve optimal results, but disparities in meeting workload expectations. Effective communication between teachers and school leaders is crucial for improvement. This research contributes significantly to understanding teacher performance in SMKs in Gunung Kidul, filling knowledge gaps and providing insights into vocational education quality at the local level.